Legal tech foreign experience (Texas Journal of Multidisciplinary Studies, 2022)
This article analyzes the use of legal tech technologies in legal practice, highlights the expediency, pros and cons of their introduction into the legal market, and modern legal tech is one of the most frequently used technologies in Russia. How does technology change legislation? What is a digital court? Is it possible to automate the work of a lawyer? We will analyze the answers to these and other questions in our article on legaltech